Slovenski glavni števniki v luči jezikovne naravnosti - Orešnik, Janez (Slavistična revija, 2001)
In Slovenia, the natural syntax of the Klagenfurt brand has been extended to "our theory", which studies the behaviour of (near-)synonymous syntactic expressions, here called syntactic variants. The theory is illustrated with morphological and (morpho)syntantic aspects of Slovenian cardinal numerals. The language material is divided into 7 "deductions" (whose subject-matter is listed in the English summary of the paper).
Keywords: glavni števnik; oblikoslovje; sintaksa; Slovene; slovenščina; števnik